3-Nitrotyrosine: a versatile oxidative stress biomarker for major neurodegenerative diseases. (2nd October 2020) - Bandookwala, Maria; Sengupta, Pinaki
Abstract: Reactive oxygen species are generated as a by-product of routine biochemical reactions. However, dysfunction of the antioxidant system or mutations in gene function may result in the elevated production of the pro-oxidant species. Modified endogenous molecules due to chemical interactions with increased levels of reactive oxygen and nitrogen species in the cellular microenvironment can be termed as biomarkers of oxidative stress. 3-Nitrotyrosine is one such promising biomarker of oxidative stress formed due to nitration of protein-bound and free tyrosine residues by reactive peroxynitrite molecules. Nitration of proteins at the subcellular level results in conformational alterations that damage the cytoskeleton and result in neurodegeneration. In this review, we summarized the role of oxidative/nitrosative processes as a contributing factor for progressive neurodegeneration in Alzheimer's disease, Parkinson's disease, Huntington's disease, Lou Gehrig's disease and Prion disease. The selective tyrosine protein nitration of the major marker proteins in related pathologies has been discussed. The alteration in 3-Nitrotyrosine profile occurs well before any symptoms appear and can be considered as a potential target for early diagnosis of neurodegenerative diseases. Furthermore, the reduction in 3-Nitrotyrosine levels in response to treatment with neuroprotective has been highlighted which is indicative of the importance of this particular marker in oxidative stress-related brain and central nervous system pathologies.